2014
DOI: 10.4103/1673-5374.147946
|View full text |Cite
|
Sign up to set email alerts
|

The effects of claudin 14 during early Wallerian degeneration after sciatic nerve injury

Abstract: Claudin 14 has been shown to promote nerve repair and regeneration in the early stages of Wallerian degeneration (0–4 days) in rats with sciatic nerve injury, but the mechanism underlying this process remains poorly understood. This study reported the effects of claudin 14 on nerve degeneration and regeneration during early Wallerian degeneration. Claudin 14 expression was up-regulated in sciatic nerve 4 days after Wallerian degeneration. The altered expression of claudin 14 in Schwann cells resulted in expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Wallerian degeneration (WD), the degeneration of the axon distal to a site of transaction, occurs in both axons and myelin after injury to the peripheral nervous system (PNS) [ 1 3 ]. The PNS, unlike the central nervous system (CNS), is capable of regeneration after an injury that causes WD processes to begin [ 4 , 5 ]. A number of studies have found that nerve injury not only plays a key role in modulating the activities of Schwann cells but also promotes axonal regeneration by releasing a large number of regeneration-related factors, including cytokines, growth factors, and chemokines [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wallerian degeneration (WD), the degeneration of the axon distal to a site of transaction, occurs in both axons and myelin after injury to the peripheral nervous system (PNS) [ 1 3 ]. The PNS, unlike the central nervous system (CNS), is capable of regeneration after an injury that causes WD processes to begin [ 4 , 5 ]. A number of studies have found that nerve injury not only plays a key role in modulating the activities of Schwann cells but also promotes axonal regeneration by releasing a large number of regeneration-related factors, including cytokines, growth factors, and chemokines [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our observations were in consistent with preceding study which showed that claudin-1 and claudin-5 proteins were down-regulated and even absent after rat sciatic nerve ligation ( Hirakawa et al, 2003 ). However, a previous study showed that CLDN14 was up-regulated in the distal nerve segments at 4 days after sciatic nerve transection ( Gong et al, 2014 ). These results seems to be contradictory with our observations since our data showed that CLDN14 was kept down-regulated in the sciatic nerve segments at 1, 4, 7, and 14 days after sciatic nerve crush.…”
Section: Discussionmentioning
confidence: 94%
“…WD is the transient and acute pathological response to peripheral nerve injury (Martini et al, 2013 ; Wu et al, 2013 ; Jung et al, 2014 ; Peluffo et al, 2015 ). Rapid developments in the field of neuroscience have led to the study of the molecular mechanism underlying many important processes (Gong et al, 2014 ; Li et al, 2015 ). We have used DNA microarray technology to detect changes in mRNA expression both in the early and late stages of WD and in the sciatic nerve of adult rats after transection.…”
Section: Discussionmentioning
confidence: 99%
“…The nerves from one group of rats were immediately used in the assays (0 h). Nerves from the other animals were used 4, 7, 14, 21 and 28 days after surgery (Hirakawa et al, 2003 ; Gong et al, 2014 ; Li et al, 2015 ). Rats in the 0 h group underwent a sham operation.…”
Section: Methodsmentioning
confidence: 99%